PENGARUH PEMERINTAHAN REZIM KHMER MERAH TERHADAP MUSLIM CHAMPA DI KAMBOJA - Bintar Mupiza (The Indonesian Islamic Studies and International Relations Association (Insiera), 2016)
Red Khmer, known as Khmer Rouge, was a military wing of Communist Party of Cambodia operated in land of Cambodia. It took power in 1975 and ended down in 1979. Khmer Rouge made tremendous human right violations in Cambodia. Under Pol Pot’s reign, Khmer Rouge turned into the bloodiest regime in Asian History. During his reign, Khmer Rouge persecuted many religious and minorities groups. One of the most persecuted whom he targeted was Chams, a Muslim ethnic. The Communist Khmer Rogue started the persecution of Chams when they took power. They destroyed mosques, burned holy Quran, and banned Chams to practice their religion so that there were significant changes over this ethnic. This paper aimed to explore Khmer Rouge influences toward Cham ethnic in Cambodia using qualitative research method by collecting data from books, journal, and online sources.